Study on Soil Macrofauna Diversity and Its Role in Litter Decomposition in Coffee-Based Agroforestry - Melda Lely Marthalina; Maroeto Maroeto; Rossyda Priyadarshini (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
The biodiversity or diversity of macrofauna depends on abiotic environmental factors and biotic environmental factors. Macrofauna plays a role in decomposing organic matter so that it can restore and maintain soil productivity. The study aims to determine the diversity of soil macrofauna in the Complex Agroforestry system and its effect on the decomposition of coffee litter. The research was carried out by observation of soil macrofauna and observation of litter decomposition rate using RAK which was composed of 2 factors, namely the type of agroforestry and the difference in the age of coffee plants. The results showed that the macrofauna diversity of soil in Complex Agroforestry and Simple Agroforestry was not different because the amount of shade and diversity were almost the same. The Soil Macrofauna Diversity Index showed a low category (H' < 2) with an average INP value of 40 – 48%. Biotic factors (litter production) and abiotic factors (temperature and humidity) affect the diversity of good macrofauna. A high macrofaunaa population will affect the rate of decomposition of debris where macrofauna plays a role in remodeling organic matter.